Pengaruh Kualitas Produk, Platform WhatsApp Business dan Word Of Mouth Terhadap Kepuasan Konsumen (Studi Pada Konsumen Umkm Di Purwokerto Barat, Banyumas, Jawa Tengah) - Nabila, Keisya Ayu; Ravindra Safitra Hidayat (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of product quality, the WhatsApp Business platform, and Word of Mouth on consumer satisfaction of MSMEs in West Purwok- erto, Banyumas, Central Java. This research employs a quantitative approach with a sample size of 100 respondents. The sampling method used is non-probability sampling with a purposive sampling technique, while the sample size was deter- mined using the Lemeshow formula.Data collection was conducted through ques- tionnaires with a Likert scale, processed using Microsoft Excel 2021 and SPSS ver- sion 26 software. The data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis test- ing. The results show that product quality and Word of Mouth variables have a significant effect on consumer satisfaction. Meanwhile, the WhatsApp Business platform variable does not have a significant effect on consumer satisfaction. These findings indicate that consumer satisfaction of MSMEs in West Purwokerto is more influenced by product quality and inter-consumer recommendations rather than the use of digital communication platforms.